2009
DOI: 10.1111/j.1439-0329.2009.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Detecting defects in conifers with ground penetrating radar: applications and challenges

Abstract: Our objective was to test ground penetrating radar (GPR) to non-destructively estimate decay volumes in living coniferous trees. GPR is geophysical tool which uses an antenna to propagate short bursts of electromagnetic energy in solid materials and measure the two-way travel time and amplitude of reflected signals. We compared estimates of bole decay from data collected with a SIR 3000 GPR system equipped with a 900 MHz antenna to measurements of decay from stem cross sections and increment cores for three co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 16 publications
1
39
0
Order By: Relevance
“…Examples of studies on discs cut out perpendicularly to the trunk axis (Nicolotti et al 2003), and on root systems (Barton & Montagu 2004, Cermak et al 2000 were found. In literature, one can also find works on the analysis of the electromagnetic wave amplitude used to locate objects' defects (Butnor et al 2009), and the effects of trees scanning using antennas with frequencies up to 1000 MHz (Lorenzo et al 2010). Careful analysis of the literature resulted in main aim of this paper -verification if the GPR method eligible for process of detection internal structure of trees for purpose of eliminating ones with inferior quality and those which can threaten public safety.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of studies on discs cut out perpendicularly to the trunk axis (Nicolotti et al 2003), and on root systems (Barton & Montagu 2004, Cermak et al 2000 were found. In literature, one can also find works on the analysis of the electromagnetic wave amplitude used to locate objects' defects (Butnor et al 2009), and the effects of trees scanning using antennas with frequencies up to 1000 MHz (Lorenzo et al 2010). Careful analysis of the literature resulted in main aim of this paper -verification if the GPR method eligible for process of detection internal structure of trees for purpose of eliminating ones with inferior quality and those which can threaten public safety.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the authors established correlations between GPR data and root biomass, finding an important relation between the root biomass and the reflected energy. The last reference we have found is attributable to Butnor et al (2009), who test GPR to non-destructively estimate decay volumes in living coniferous trees.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, most of radar waves were reflected when encountered a mental plate. Thus, the propagation velocity and the average dielectric constant of trees could be calculated by the two-way travel time in the known distance (diameter trees) [10]. …”
Section: Gpr Systemmentioning
confidence: 99%